Tracking Risk for Crime Throughout the Day: An Examination of Jersey City Robberies. (June 2021) - Caplan, Joel M.; Neudecker, Christine H.; Kennedy, Leslie W.; Barnum, Jeremy D.; Drawve, Grant
This study examines temporal variations in the spatial influence of environmental features, such as bars and vacant buildings, on criminal behavior across microlevel places. Specifically, 17 environmental risk factors and their spatial influences are identified for calendar year 2014 street robberies in Jersey City, NJ. To explore temporal variation, risk factors and their spatial influences on crime are identified across 12 discrete 2-hr time intervals. The results demonstrate that the risk factors for street robbery varied across the course of a day. In fact, mapping the most vulnerable places for street robbery revealed that while many of the same environmental features remain high risk throughout the day, their influence varied. These results suggested that there was a temporality to robbery and that it is likely due to the interaction between physical vulnerabilities from the built environment and social behaviors of people at these places. This demonstrates the importance of considering the temporal dimension of criminal behavior as results show that people use and interact with their environment differently throughout the course of the day.